2005
DOI: 10.1300/j465v25n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Development in Small-Group Teaching Skills Associated with a Training Course on Office-Based Treatment of Opioid Dependence

Abstract: The Drug Addiction Treatment Act of 2000 (DATA-2000) allows qualified physicians to treat opioid-dependent patients with schedule III-V medications, such as buprenorphine, in practices separate from licensed, accredited opioid treatment programs. Physicians may attain this qualification by completing 8-hours of training in treating opioid dependence. This paper describes the evaluation of a faculty development workshop designed to enhance teaching skills of small-group facilitators involved with DATA-2000 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…We found that while immediately highly popular, the knowledge obtained in the VHA‐EES‐BTP translated into only a few physicians receiving the waiver to prescribe and still fewer physicians prescribing buprenorphine. Similar to other reports in the literature, 6, 9 we found that all of the respondents reported that the eight‐hour programs were worthwhile and compared favorably to other CME activities. All of the respondents reported they fully accomplished and felt competent to apply the program objectives regarding the treatment of opioid dependence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that while immediately highly popular, the knowledge obtained in the VHA‐EES‐BTP translated into only a few physicians receiving the waiver to prescribe and still fewer physicians prescribing buprenorphine. Similar to other reports in the literature, 6, 9 we found that all of the respondents reported that the eight‐hour programs were worthwhile and compared favorably to other CME activities. All of the respondents reported they fully accomplished and felt competent to apply the program objectives regarding the treatment of opioid dependence.…”
Section: Discussionsupporting
confidence: 88%
“…The VHA‐EES‐BTPs were designed to provide information and training on the office‐based treatment of opioid dependence using buprenorphine. The American Society of Addiction Medicine was the certifying organization, and course content was consistent with other DATA 2000 certification trainings 9 . At the completion of the courses, physicians were asked to complete the DATA 2000 certification form, and the VHA‐EES informed the Substance Abuse and Mental Health Services Administration of their participation.…”
Section: Methodsmentioning
confidence: 99%
“…Specialty-specific project faculty were then identified and supported by the grant in each specialty ( Figure 1). Following an established method, the senior core faculty organized several "train the trainer" sessions for the team leaders, who then took responsibility for organizing and training the residents and residency program faculty when possible to enhance continual role modeling and resident observation in the clinical setting (52). In addition, the SBIRT faculty (core and project faculty) developed a curriculum Web site (www.yale.edu/sbirt), which included specialty-specific modules and cases, training manuals, readings, screening tools, slide presentations, and video clips of real patient scenarios of the BNI.…”
Section: Curriculum Implementationmentioning
confidence: 99%
“…Other faculty development interventions have demonstrated effectiveness in improving faculty opioid prescribing skills [29,45] and screening for at-risk substance use and substance use disorders (using screening, brief intervention, and referral to treatment [SBIRT]) [46]. However, these interventions have not shown improvements in teaching residents.…”
Section: Discussionmentioning
confidence: 99%